Implementasi Sistem Otomatis Pada Conveyor Bandar Udara Rahadi Oesman Ketapang - Yudi Chandra (Electrical Network Systems and Sources, 2022)
Baggage handling has an important role in maintaining the comfort of passengerstraveling by airplane and processing the baggage until it can be transported together on the same plane with the passengers. But so far, passengers don't knowhow to process the luggage that has been handed over at the check-in counter tothe plane's baggage. But so far, passengers don't know how to process luggage from planes to passengers. Along with the growth of flight movements (passengers and aircraft), currently the technology applied to handling passenger baggage has developed rapidly.The current conveyor system runs continuously, whether thereare goods or not, to turn off the conveyor still uses human/operator power. If theoperator is careless/less orderly can lead to human error so that the increased useof electricity. One of the services that use conveyor systems such that Rahadi Oesman Airport Ketapang. Of these problems, the system is designed to automatically on the conveyor. This design has been in system tools automatically on a conveyor that can be turn on without pressing the start button if the storage detected the presence of goods and conveyor can die without pressingthe stop button when the trunk does not detect the presence of goods that are processed by the Proximity Sensor Retroreflecting. The system automaticallyon the conveyor can be applied in Rahadi Oesman airport Ketapang to facilitate the performance of technicians and electricity saving.